Mobile learning in Malaysian Technical and Vocational Education (TVE): a qualitative case study - Abd Rahman, Rossyahida (2011)
Mobile learning is not learning through mobile phones or learning over a wireless connection even though the capabilities of running multimedia features has increased in recent years. But mobile learning is the evolution of e-learning, which completes the missing component of an e-learning solution. Mobile learning most suits for those mobile parties in education institutes. So, utilizing mobile devices in education is mainly considered as enhanced tools. Innovations in mobile learning can lead to a change paradigm in education which mobile technologies are believed to have the potential to be used in teaching and learning in schools. This paper discusses the feasibility of employing mobile phones for mainstream schooling in Malaysian Technical and Vocational Education and Training (TVET). The paper describes the various perceptions of the use of mobile phones for learning by reflecting on the positive opinion from educational researchers around the world, including Malaysia. Current initiatives in the use of mobile phones for teaching and learning are explored. Beside discuss about the advantages, disadvantages and tools for mobile learning this paper also explore about the possibilities using mobile learning in technical and vocational mainstream.